Cardiovascular risk assessment: The foundation of preventive cardiology - Wong, Nathan D. (Am J Prev Cardiol, 2020)
The foundation of preventive cardiology begins with knowing the patient’s baseline cardiovascular disease (CVD) risk from which the patient-clinician risk discussion informs on the best ways to lower risk through lifestyle management, as well as a decision about the initiation and intensity of pharmacologic therapy. Global CVD risk assessment involves estimation of cardiovascular risk using a basic panel of risk factors. The Framingham Heart Study championed the first such risk scores, followed by others around the world. Most recently, the Pooled Cohort Equations (PCE) have been recommended in the United States as a starting point in CVD risk assessment. Persons at low (<5%) 10-year risk are generally recommended for lifestyle management only and those at highest (>20%) 10-year risk are recommended for both lifestyle and pharmacologic therapy to reduce risk. Assessing the presence of one or more “risk enhancing” factors is intended to inform the treatment decision in those at borderline (5-<7.5%) or intermediate (7.5–20%) risk, with the use of coronary calcium scores to further refine the treatment decision. Moreover, not all those with ASCVD are treated equal, and recent guidelines provide criteria for identifying those at very high risk. While current techniques best predict long-term risk of CVD events, biomarkers strategies are being developed to predict near-term events, and other imaging techniques such as coronary CT angiography and vascular MRI hold promise to identify vulnerable plaque. Validation and incorporating into clinical practice such state of the art techniques will be vital to moving CVD risk assessment to the next level.